Households' acceptability of local (Ofada) rice based on quality attributes in South-West, Nigeria. Issue 9 (1st August 2019) - Ogunleke, Ayodeji Oluwaseun; Baiyegunhi, L.J.S.
Abstract : Purpose: The purpose of this paper is to examine households' acceptability of local (Ofada) rice by identifying the quality attributes influencing marginal implicit prices (MIPs) paid by rice consumers' households in South-West, Nigeria. Design/methodology/approach: The data used for this study were collected from a survey of 600 rice-consuming households in the study area. A multistage sampling technique was employed to select the respondents. Well-structured questionnaires were used to collect information on general households' socioeconomic characteristics, their desirability and preference for local (Ofada) rice, and market prices of Ofada rice. Kendall's concordance test was performed to confirm agreement among respondents in their rankings of the rice quality attributes. Hedonic price function was used to examine the relationship between implicit prices paid by consumers based on quality attributes of local (Ofada) rice, as observed in the market. Findings: The result of Kendall's coefficient of concordance revealed that there is 73.74 per cent agreement in ranking quality attributes of local (Ofada) rice consumers' households in the study area. Colour, perceived nutrient level, taste, grain shape and rate of breakage were the most ranked quality attributes with mean attribute ranking scores of 1.56, 1.69, 3.12, 5.53 and 5.86, respectively. The result of the hedonic pricing model revealed that households are willing to pay MIPs of ₦71.03 ($0.20), ₦45.23 ($0.13), ₦32.98 ($0.09), ₦21.06 ($0.06) and ₦14.41($0.04) per kg for colour, grain cohesion, grain shape, perceived nutrient level and perceived chemical storage, respectively, while discounting MIPs of ₦60.55 ($0.17), ₦19.36 ($0.05), ₦17.14 ($0.05) and ₦6.00 ($0.02) for texture, rate of breakage, perceived freshness and low swelling capacity per kg of local (Ofada) rice, respectively. Research limitations/implications: Continuous importation of rice into the country has many negative implications such as worsening of the poverty status of local rice farmers, unemployment of teeming youths engaged in rice value chain, and exposure to soaring and unpredictable price bringing unsustainable development. Lastly, over-dependency on rice importation, if not checked, can also permit dumping of low quality and sometimes expired rice into the country. All aforementioned reasons will make it difficult for local rice to compete favourably with imported varieties. Practical implications: Kendall's coefficient of concordance and Hedonic model were used as a diagnostic tools. These diagnostic tools show the need for government and relevant stakeholders to focus on improving the quality of local (Ofada) rice, especially the undesirable attributes. This could be achieved by adopting modern processing technology, that will enhance production and consumers' acceptability, which could make local (Ofada) rice have good market share against imported brands. Social implications: The economic value of a good is revealed by the consumer's willingness to pay for the good, consequently increasing production through consumers' acceptability, and improve living standard of farmers and processors through increased earnings. Originality/value: The choice of a particular local rice, especially local (Ofada) rice, is made to estimate the effect of different attributes on the price paid by rice consumers' households and to help in the development of effective technologies and policy that enhance better rice quality using both Kendall's coefficient of concordance and Hedonic model to achieve the objective. For the first time this research has given clarity on the monetary value attached to local (Ofada) rice consumption by rice consumers' households through quality attributes.